EFEKTIVITAS EKSTRAKULIKULER BTQ DALAM MENINGKATKAN KOMPETENSI MEMBACA AL-QUR’AN PESERTA DIDIK DI SMPN 9 REJANG LEBONG - SITI SAPUROH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Al-Qur'an education is very important for children, especially junior high school students. At this age they should be able to read and write the Qur'an. But seeing the reality they have not been able to learn to read the Qur'an properly. Therefore, SMPN 9 Rejang Lebong organizes BTQ extracurricular activities so that students who are not fluent in reading and writing the Qur'an and cannot read and write the Qur'an at all can improve their competence in reading and writing the Qur'an. This study has a purpose, namely to describe the implementation of Al-Qur'an Reading and Writing at SMPN 9 Rejang Lebong and also to find out the effectiveness of Al-Qur'an Reading and Writing in improving the ability to read the Qur'an at SMPN 9 Rejang Lebong. This research belongs to the type of descriptive qualitative research with the research subject of students who take extracurricular activities. Data was collected using the methods of observation, interviews and documentation. The data obtained were then analyzed using qualitative descriptive analysis including data reduction, data display, and data verification (conclusion drawing/verification). From the data presented, there are positive changes shown by students in the context of the ability to read the Qur'an where during the first semester there were not a few students who were not fluent in reading the Qur'an and in the second semester there were more students. who is quite fluent in reading the Qur'an. This is indicated by the percentage that of the 25 students in class VII and class VIII who take part in Extracurricular Al-Quran Reading and Writing activities, there are 14 students whose ability to read Al-Quran has increased. The following are the results of the calculation of the percentage increase in the ability to read the Koran for class VII and class VIII at SMPN 9 Rejang Lebong 56%. ABSTRAKPendidikan Al-Qur’an sangatlah penting bagi anak-anak terutama anak SMP. Pada usia ini hendaknya mereka sudah mampu membaca dan menulis Al-Qur’an. Tetapi melihat realitanya mereka belum mampu Belajar Membaca al-Qur’andengan baik. Maka dari itu SMPN 9 Rejang Lebong menyelenggarakan kegiatan ekstrakurukuler BTQ agar peserta didik yang belum lancar membaca dan menulis Al-Qur’an dan tidak bisa sama sekali membaca dan menulis Al-Qur’an dapat meningkatkan kompetensi membaca dan menulis Al-Qur’an. Penelitian ini memiliki tujuan yaitu untuk mendeskripsikan pelaksanaan Baca Tulis al-Qur’an di SMPN 9 Rejang Lebong dan juga untuk mengetahui sejauh mana Efektivitas Baca Tulis al-Qur’an dalam meningkatkan kemampuan membaca Al-Qur’an di SMPN 9 Rejang Lebong. Penelitian ini termasuk jenis penelitian deskriptif kualitatif dengan subjek penelitian peserta didik yang mengikuti ekstrakulikuler. Pengumpulan data dilakukan dengan menggunakan metode observasi, wawancara dan dokumentasi. Data yang diperoleh selanjutnya, dianalisis menggunakan analisis deskriptif kualitatif di antaranya, reduksi data (data reduction), Penyajian data (data display), dan Verifikasi data (conclusion drawing/verification). Dari data yang dipaparkan, terdapat perubahan yang positif yang ditunjukkan peserta didik dalam konteks kemampuan membaca al-Qur’an dimana pada saat semester satu tidak sedikit peserta didik yang belum lancar membaca al-Qur’an dan pada saat semester dua sudah lebih banyak peserta didik yang cukup lancar membaca al-Qur’an. Hal ini ditunjukkan dengan prosentase bahwa dari 25 peserta didik dikelas VII dan kelas VIII yang mengikuti kegiatan Ekstrakulikuler Baca Tulis Al-Quran, terdapat 14 peserta didik yang kemampuan membaca al-Qurannya meningkat. Berikut hasil perhitungan prosentase peningkatan kemampuan membaca alQuran kelas VII dan kelas VIII di SMPN 9 Rejang Lebong 56 %.